(untitled) (Darya Ganj, New Delhi, 2005)
Contents of material: Library and higher education. Changing trends of librarianship. Online library management. New documentation technology. Documentation culture. Digitisation of information. Technology and communication. Digital archivies. Technology transfer. Challenges of digital technology.
Keywords: Libraries,Library information networks,Integrated library systems ( Computer systems ),Digital libraries; Automation